The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2011
DOI: 10.1007/s11869-010-0131-2
|View full text |Cite
|
Sign up to set email alerts
|

Global review of national ambient air quality standards for PM10 and SO2 (24 h)

Abstract: Literature comparing national ambient air quality standards (AAQSs) globally is scattered and sparse. Twenty-four hour AAQSs for particulate matter <10 μm in aerodynamic diameter (PM10) and sulfur dioxide (SO2) in 96 countries were identified through literature review, an international survey, and querying an international legal database. Eighty three percent, of the 96 countries with information on the presence or absence of AAQSs, have 24-h AAQSs for either PM10 or SO2. Slightly more countries have 24-h AAQS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
39
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(42 citation statements)
references
References 2 publications
1
39
0
1
Order By: Relevance
“…Since 1987, World Health Organization (WHO) published guidelines for air quality are reviewed periodically (91,92) . Similar guidelines, some with differences in items monitored or cut-off levels are provided by the Environmental Protection Agency (EPA) from the USA and other national or continental agencies (Table 5).…”
Section: Environment Monitoring Toolsmentioning
confidence: 99%
“…Since 1987, World Health Organization (WHO) published guidelines for air quality are reviewed periodically (91,92) . Similar guidelines, some with differences in items monitored or cut-off levels are provided by the Environmental Protection Agency (EPA) from the USA and other national or continental agencies (Table 5).…”
Section: Environment Monitoring Toolsmentioning
confidence: 99%
“…In a previous study, we showed that high local knowledge production in the field of air pollution was correlated with better local air quality at the national level (Fajersztajn, et al, 2013). Nawrot and colleagues (2011) showed that air pollution is an important trigger of myocardial infarction, similar in magnitude to other well-accepted risk factors (e.g., physical exertion and alcohol consumption), but the stringency of national air quality standards remains greatly different among countries (Vahlsing & Smith 2012). Scientists began to associate tobacco with severe health impacts in the early 50s (Doll & Hill, 1954), but important health-related polices were not implemented in some cities for a long time or were not implemented at all in other cities.…”
Section: Introductionmentioning
confidence: 92%
“…A disadvantage of current efforts to apply a standardised interpretation of data is that data from monitoring networks set up to achieve similar goals are often interpreted in different ways, making comparison between networks difficult. For example, differences in air quality standards between two monitoring networks make interpretation of the relative air quality situation in each country difficult [24,175]. Additionally, standard analyses of data across multiple monitoring sites generally either focus on the quantification of a particular impact or comparison with air quality targets [113,152,173], or on spatial and temporal variation in atmospheric constituents generally [160,176], rather than a holistic characterisation of both an impact of atmospheric composition, and the conditions producing it.…”
Section: Current State Of Monitoring Networkmentioning
confidence: 99%
“…For example, many countries have policies aimed at reducing emissions of air pollutants associated with poor air quality [23,24], whereas increasing urbanisation, especially in developing nations, could increase air pollution [25]. Climate change will also change atmospheric composition [26,27].…”
Section: Introductionmentioning
confidence: 99%